Introduction - Mancini, Paolo (Sociologija. Mintis ir veiksmas, 2015)
Introduction to a special issue of “Sociologija. Mintis ir veiksmas” that contains a number of original papers presented at the international conference “European Public Spheres, Civil Society and Civic Mass Media“, organized by Vytautas Magnus University, Kaunas in April 2007.